Exploring the use of rapport in professional information‐gathering contexts by systematically mapping the evidence base. Issue 2 (19th November 2020) - Gabbert, Fiona; Hope, Lorraine; Luther, Kirk; Wright, Gordon; Ng, Magdalene; Oxburgh, Gavin
Summary: A growing body of research illustrates consensus between researchers and practitioners that developing rapport facilitates cooperation and disclosure in a range of professional information gathering contexts. In such contexts, rapport behaviors are often intentionally used in an attempt to facilitate a positive interaction with another adult, which may or may not result in genuine mutual rapport. To examine how rapport has been manipulated and measured in professional contexts we systematically mapped the relevant evidence‐base in this field. For each of the 35 studies that met our inclusion criteria, behaviors associated with building rapport were coded in relation to whether they were verbal, non‐verbal, or para‐verbal. Methods to measure rapport were also coded and recorded, as were different types of disclosure. A Searchable Systematic Map was produced to catalogue key study characteristics. Discussion focuses on the underlying intention of the rapport behaviors that featured most frequently across studies.